Dexmedetomidine Pharmacokinetics and a New Dosing Paradigm in Infants Supported With Cardiopulmonary Bypass. (December 2019) - Zimmerman, Kanecia O.; Wu, Huali; Laughon, Matthew; Greenberg, Rachel G.; Walczak, Richard; Schulman, Scott R.; Smith, P. Brian; Hornik, Christoph P.; Cohen-Wolkowiez, Michael; Watt, Kevin M.
Abstract : BACKGROUND: Dexmedetomidine is increasingly used off-label in infants and children with cardiac disease during cardiopulmonary bypass (CPB) and in the postoperative period. Despite its frequent use, optimal dosing of dexmedetomidine in the setting of CPB has not been identified but is expected to differ from dosing in those not supported with CPB. This study had the following aims: (1) characterize the effect of CPB on dexmedetomidine clearance (CL) and volume of distribution (V) in infants and young children; (2) characterize tolerance and sedation in patients receiving dexmedetomidine; and (3) identify preliminary dosing recommendations for infants and children undergoing CPB. We hypothesized that CL would decrease, and V would increase during CPB compared to pre- or post-CPB states. METHODS: Open-label, single-center, opportunistic pharmacokinetics (PK) and safety study of dexmedetomidine in patients ⩽36 months of age administered dexmedetomidine per standard of care via continuous infusion. We analyzed dexmedetomidine PK data using standard nonlinear mixed effects modeling with NONMEM software. We compared model-estimated PK parameters to those from historical patients receiving dexmedetomidine before anesthesia for urologic, lower abdominal, or plastic surgery; after low-risk cardiac or craniofacial surgery; or during bronchoscopy or nuclear magnetic resonance imaging. We investigated the influence of CPB-related factors on PK estimates and used the final model to simulate dosing recommendations, targeting a plasma concentration previously associated with safety and efficacy (0.6 ng/mL). We used the Wilcoxon rank sum test to evaluate differences in dexmedetomidine exposure between infants with hypotension or bradycardia and those who did not develop these adverse events. RESULTS: We collected 213 dexmedetomidine plasma samples from 18 patients. Patients had a median (range) age of 3.3 months (0.1–34.0 months) and underwent CPB for 161 minutes (63–394 minutes). We estimated a CL of 13.4 L/h/70 kg (95% confidence interval, 2.6–24.2 L/h/70 kg) during CPB, compared to 42.1 L/h/70 kg (95% confidence interval, 38.7–45.8 L/h/70 kg) in the historical patients. No specific CPB-related factor had a statistically significant effect on PK. A loading dose of 0.7 µg/kg over 10 minutes before CPB, followed by maintenance infusions through CPB of 0.2 or 0.25 µg/kg/h in infants with postmenstrual ages of 42 or 92 weeks, respectively, maintained targeted concentrations. We identified no association between dexmedetomidine exposure and selected adverse events ( P = .13). CONCLUSIONS: CPB is associated with lower CL during CPB in infants and young children compared to those not undergoing CPB. Further study should more closely investigate CPB-related factors that may influence CL.